Strengthening tourism in the post-conflict (2015)
In the present work aims to expose and to sign the peace agreement between the Colombian government and the guerrillas of the Revolutionary Armed Forces of Colombia ( FARC ) , it was to symbolize not only a territory free of paramilitary and guerrilla presence but also a free territory violence, it is expected to lose their fear tourists to visit the country , it could be attributed to tourism the country's transformation